Development of lipid productivities under different CO2 conditions of marine microalgae Chlamydomonas sp. JSC4 - Nakanishi, Akihito; Aikawa, Shimpei; Ho, Shih-Hsin; Chen, Chun-Yen; Chang, Jo-Shu; Hasunuma, Tomohisa; Kondo, Akihiko (Bioresource technology, 2014)
•Chlamydomonas sp. JSC4 was isolated from southern Taiwan sea coast.•Lipid productivity was assayed after cultivation under different CO2 concentrations.•Lipid productivity was 169.1mg/L/d as the best in most of the previous reports.•Result showed a potential to develop the system of microalga-based lipid production. Biodiesel production from microalgae has become a popular research topic. In this study, Chlamydomonas sp. JSC4 isolated from the southern coast of Taiwan was selected for a detailed study on cell growth and lipid accumulation under marine salinity (3.5% sea salt). Proper CO2 was supplied as the improvement of lipid productivity. Under the optimal condition, the highest lipid productivity was 169.1mg/L/d, which was significantly higher than those reported in current studies for marine green algae. To date, only very few studies have reported a marine algae strain with both high cell growth and lipid productivity. This study demonstrated that a newly isolated marine green alga Chlamydomonas sp. JSC4 would be a feasible oil producer due to its high biomass production and lipid productivity under marine salinity.